2022
DOI: 10.1037/edu0000744
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the let’s know! Curriculum on the language and comprehension-related skills of prekindergarten and kindergarten children.

Abstract: Educational Impact and Implications StatementDespite improvements in word-level reading instruction, many children continue to struggle with reading comprehension. In this study, we tested a whole-class, supplemental curriculum, Let's Know!, designed to support prekindergarten and kindergarten children's oral language and comprehension skills. We found that Let's Know! improved children's knowledge of vocabulary used in the curriculum and some comprehension-related skills but did not impact scores on standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Furthermore, what is abundantly clear is that young children with weaker language skills are vulnerable to later difficulties in acquiring academic and interpersonal proficiencies expected for later school and career success (e.g., Bleses et al, 2016; Ricciardi et al, 2021). In agreement with many others, we conceptualize language to include foundational skills of vocabulary, syntax, morphological knowledge, phonology, and pragmatics, while also recognizing the comprehension-specific skills including inferencing, comprehension monitoring, and text structure knowledge that operate in both listening and reading contexts (e.g., Krenca et al, 2023; Language and Reading Research Consortium et al, 2022).…”
Section: Challenges Associated With Language Weaknessesmentioning
confidence: 86%
“…Furthermore, what is abundantly clear is that young children with weaker language skills are vulnerable to later difficulties in acquiring academic and interpersonal proficiencies expected for later school and career success (e.g., Bleses et al, 2016; Ricciardi et al, 2021). In agreement with many others, we conceptualize language to include foundational skills of vocabulary, syntax, morphological knowledge, phonology, and pragmatics, while also recognizing the comprehension-specific skills including inferencing, comprehension monitoring, and text structure knowledge that operate in both listening and reading contexts (e.g., Krenca et al, 2023; Language and Reading Research Consortium et al, 2022).…”
Section: Challenges Associated With Language Weaknessesmentioning
confidence: 86%
“…A recent meta-analysis on the impact of vocabulary instruction on passage comprehension found that vocabulary interventions had large effect sizes (ES) on custom measures, most often proximal, and small ES on standardized distal measures (Wright & Cervetti, 2017). Furthermore, recent findings from the Let’s Know intervention—a key program from the RfU initiative—showed that there were no significant effects on language comprehension, nor did vocabulary knowledge have a significant indirect effect on language comprehension outcomes (Language and Reading Research Consortium et al, 2022). Building science and social studies topic knowledge takes time in the early grades (Cabell & Hwang, 2020) and most studies examine effects after only 1 year of intervention implementation.…”
Section: Theoretical Foundation Of Content Literacy Interventionmentioning
confidence: 99%
“…Due to COVID-19 school closures, however, we were unable to directly assess the quality of teachers’ vocabulary instruction through classroom observations and audio recordings of lessons. Consistent with other classroom-based interventions that examine the mediating effects of vocabulary learning on students’ reading comprehension (Clarke et al 2010; Cromley & Azevedo, 2007; Language and Reading Research Consortium et al, 2019, 2022), it is critical to address this limitation with multilevel SEMs (Preacher et al, 2010) that jointly model the mediating effects of both Level 1 student variables and Level 2 classroom-teacher variables. Doing so would paint a richer and perhaps more complete picture of the dynamic student and teacher variables that interact to ultimately improve students’ reading comprehension.…”
Section: Study Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation